Structural overloading evaluation based on the identification of subcritical crack increments. (October 2015) - Sedek, Jakub; Behal, Jiri; Siegl, Jan
Highlights: Tear bands were observed on failure surfaces on aluminium alloy parts of root spar assembly of the wrecked wing. Overloading level and tear bands size are determined by numerical iterative solution. R curve concept utilized for tear band prediction. Abstract: A complex approach using fractographic and FE analysis was used to assess the load level of a lower root spar assembly under conditions, which were close to the critical load of the structure. A Damage Tolerance scheme of determining the conditions for subcritical crack increments was used. The stress state for the measured subcritical increments in an airplane structure was determined using a proposed iterative solution to match the material R curve to the J -integral solution. A structural stress analysis of the root of the wing structure assigned a load level to the crack state identified above. The numerical FE solutions of the J -integral along the identified crack fronts were generated using ABAQUS SW at the Strength of Structures Dpt., Aerospace Research and Test Establishment. The analysis provides information regarding the near-critical loading condition of the wing structure.